Methodology to minimize the dynamic response of tall buildings under wind load controlled through semi-active magneto-rheological dampers - Alex Koch de Almeida; Francisco da Silva Brando; Letcia Fleck Fadel Miguel (Fracture and Structural Integrity)
This paper proposes a methodology to evaluate and optimize the dynamic response of tall buildings under wind loading, controlled through semi-active Magneto-Rheological dampers (MR dampers). For this, a tall building, modeled as a 2D frame, is taken as case study and three structural control configurations are proposed. The original structural configuration of the building is the first configuration analyzed, called Uncontrolled Original (C1). In the second configuration, called Uncontrolled Optimized (C2), the fundamental frequency of the building is optimized via PSO algorithm as a function of its mass. Then, in the third configuration, Controlled Optimized (C3), a set of MR dampers with behavior formulated via the modified Bouc-Wen rheological model and controlled through the Linear Quadratic Regulator associated with the Clipped Optimal control strategy (LQR-CO) is applied to the structure. Finally, the dynamic response of the three scenarios under wind action is analyzed and compared to performance criteria established in the literature. The results demonstrate that the C3 configuration is the only one able of satisfying all the established performance criteria, proving that the proposed methodology y that combines structural optimization with MR dampers is a powerful tool for vibration control.